Analisis Ekosistem Seni Raprock United Bali - Ricky Fernando; I Wayan Mudra; I Ketut Sariada (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Raprock United Bali is an important music community that plays a significant role in preserving and promoting the rap rock genre in Bali. Since its formation in 2015, this community has served as a platform for musicians and rap rock enthusiasts to create, collaborate, and maintain the genre's presence amid shifting musical preferences within society. This study aims to analyze the role of Raprock United Bali within the cultural, social, economic, educational, and legal ecosystems, as well as the community's strategies for addressing various challenges. Using a descriptive qualitative method, data was collected through interviews with community members and literature analysis. The research findings indicate that Raprock United Bali has a strong cultural ecosystem through regular activities such as RAPROCK NIGHT and the production of the compilation album “ROKIN RAPROCK,” supported by local sponsors. In the social ecosystem, this community strengthens solidarity among members and builds connections with audiences through music events that also impact the local economy. Additionally, the community contributes to knowledge transfer and musical skill development, making it an informal educational platform for its members. Awareness of copyright protection and licensing regulations is also a crucial aspect of the community's legal sustainability. In conclusion, Raprock United Bali is not only a driving force in the music scene but also creates a significant impact on Bali's cultural ecosystem and society, making it an inspiring model for other art communities in Indonesia.